2015
DOI: 10.1093/nar/gkv1045
|View full text |Cite
|
Sign up to set email alerts
|

Expression Atlas update—an integrated database of gene and protein expression in humans, animals and plants

Abstract: Expression Atlas (http://www.ebi.ac.uk/gxa) provides information about gene and protein expression in animal and plant samples of different cell types, organism parts, developmental stages, diseases and other conditions. It consists of selected microarray and RNA-sequencing studies from ArrayExpress, which have been manually curated, annotated with ontology terms, checked for high quality and processed using standardised analysis methods. Since the last update, Atlas has grown seven-fold (1572 studies as of Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
450
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 512 publications
(474 citation statements)
references
References 29 publications
16
450
0
1
Order By: Relevance
“…Specifically, we evaluated FAD2 mRNA levels by qRT-PCR using RNA isolated from the dissected scutellar and radicle tissues. Bioinformatic analysis of maize genome data (Sen et al, 2010;Petryszak et al, 2016) identified six putative FAD2 genes based upon sequence homology to the Arabidopsis FAD2 gene (At3g12120); these were annotated as GRMZM2G169240, GRMZM2G169261, GRMZM2G174766, GRMZM2G056252, GRMZM2G161792, and GRMZM2G064701. Initial assays (Supplemental Table S5) identified that only GRMZM2G056252 and GRMZM2G064701 are expressed at measurable levels in germinating embryonic tissue during the initial 36 h after imbibition; the expression of the other four FAD2-like genes was detectable by RT-PCR, but their levels were too low to obtain robust quantitative expression data.…”
Section: Differential Distributions Of Lipid Classes Accentuated In Tmentioning
confidence: 99%
“…Specifically, we evaluated FAD2 mRNA levels by qRT-PCR using RNA isolated from the dissected scutellar and radicle tissues. Bioinformatic analysis of maize genome data (Sen et al, 2010;Petryszak et al, 2016) identified six putative FAD2 genes based upon sequence homology to the Arabidopsis FAD2 gene (At3g12120); these were annotated as GRMZM2G169240, GRMZM2G169261, GRMZM2G174766, GRMZM2G056252, GRMZM2G161792, and GRMZM2G064701. Initial assays (Supplemental Table S5) identified that only GRMZM2G056252 and GRMZM2G064701 are expressed at measurable levels in germinating embryonic tissue during the initial 36 h after imbibition; the expression of the other four FAD2-like genes was detectable by RT-PCR, but their levels were too low to obtain robust quantitative expression data.…”
Section: Differential Distributions Of Lipid Classes Accentuated In Tmentioning
confidence: 99%
“…Processing of over 55 million tandem mass spectra from different publicly available datasets using OpenMS led them to discover over 40 new protein-coding gene annotations in the GENCODE human reference genome [45] . In addition to the identification of novel genes, the information gained in a proteogenomic analysis pertaining to known proteins can also be utilized, for example, to elucidate tissue-specific protein expression levels [46] .…”
Section: Swath Data Analysismentioning
confidence: 99%
“…(Zhao et al, 2014) Ferritin up-regulation occurred after SPION and Au-NP treatment, and similar effects were observed after C. elegans exposure to arsenic, cadmium and ethosuximide. (Chen et al, 2013, Chen et al, 2015, Petryszak et al, 2016 Hence, the effects of SPIONs in iron homeostasis might be part of a more general response to toxicants and not necessarily linked to oxidative dissolution of the SPION core into free iron.…”
Section: Evaluation Of Specific Molecular Markersmentioning
confidence: 99%